PENGARUH KEPEMILIKAN MANAJEMEN, JENIS INDUSTRI, DIVERSIFIKASI PRODUK, PROFITABILITAS, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO PADA INDUSTRI PERBANKAN DAN MANUFAKTUR - Ulfiana Melani; Muh Al Amin (Universitas Ahmad Dahlan, 2016)
This study aims to examine the effect of management ownership, type of industry, product diversifi cation, profi tability, and fi rm age to risk management disclosure on the annual reports of the companies that listed in BEI 2010-2014. The data of this study is secondary data. Sample of this study used bank industry and manufacturing industry that listed in BEI from 2010 until 2014. Sampling methode of this study used purposive sampling and get 30 companies. The statistics methode used multiple linear regression analysis. The result showed that management ownership, type of industry, profi tability, and fi rm age have no effect to risk management disclosure. This study also showed that all variables has effect to risk management disclosure and the models of the study has goodness of fi t.